The Regional Dimension of International Joint Ventures in Emerging Markets: A Comparison of Managerial Perception of Vietnam and Cote D’lvoire - Frank L. Bartels; Nick J. Freeman (Asian Academy of Management Journal, 1998)
The Regional Dimension of International Joint Ventures in Emerging Markets: A Comparison of Managerial Perception of Vietnam and Cote D’lvoire (PDF not available)